Comparative mRNA Expression of eEF1A Isoforms and a PI3K/Akt/mTOR Pathway in a Cellular Model of Parkinson’s Disease - Kawinthra Khwanraj; Suriyat Madlah; Khwanthana Grataitong; Permphan Dharmasaroja (Parkinson's Disease)
The PI3K/Akt/mTOR pathway is one of dysregulated pathways in Parkinson’s disease (PD). Previous studies in nonneuronal cells showed that Akt regulation can be increased by eukaryotic protein elongation factor 1 alpha 2 (eEF1A2). eEF1A2 is proposed to contribute protection against apoptotic death, likely through activation of the PI3K/Akt pathway. Whether eEF1A2 plays a role in the prevention of cell death in PD has not been investigated. Recently, gene profiling on dopaminergic neurons from postmortem PD patients showed both upregulation and downregulation of some PI3K and mTOR genes. In this paper, the expression of all gene members of the PI3K/Akt/mTOR pathway in relation to those of the eEF1A isoforms in a cellular model of PD was investigated at the mRNA level. The results showed a similar trend of upregulation of genes of the eEF1A isoforms (eEF1A1 and eEF1A2) and of the PI3K (classes I–III)/Akt (Akt1, Akt2, and Akt3)/mTOR (mTORC1 and mTORC2) pathway in both nondifferentiated and differentiated SH-SY5Y dopaminergic cells treated with 1-methyl-4-phenylpyridinium (MPP+). Upregulation of eEF1A2, Akt1, and mTORC1 was consistent with the relative increase of eEF1A2, Akt, phospho-Akt, and mTORC1 proteins. The possible role of eEF1A isoforms in the regulation of the PI3K/Akt/mTOR pathway in PD is discussed.